2020
DOI: 10.5658/wood.2020.48.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril Angle Characteristics of Korean Pine Trees from Depending on Provinces

Abstract: This study investigated the characteristics of microfibril angle(MFA) in order to see if there was any difference in pine tree lumber quality among the three mountain areas surrounding the Taebaek Mountains in Korea -Yeongdong (Goseong-gun), Yeongseo (Hongcheon-gun) and Yeongnam (Bonghwa-gun). Pine trees of each mountain area were divided into earlywood and latewood in relation to heartwood part (1959 ∼ 1961, 3 annual rings) and sapwood part (2002 ∼ 2004, 3annual rings), and measured at tangential section. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In 70-year-old teak trees in East Timor, the average proportion of stands' heartwood was ± 40% higher than the findings in this study (Miranda et al, 2011). This discrepancy was presumably caused by various influences, i.e., differences in the growth rate, type of stands, characteristics of the individual tree, age, genotype, topography, and site quality (Huh et al, 2020;Kim et al, 2020aKim et al, , 2020bPinto et al, 2004).…”
Section: Discussioncontrasting
confidence: 66%
“…In 70-year-old teak trees in East Timor, the average proportion of stands' heartwood was ± 40% higher than the findings in this study (Miranda et al, 2011). This discrepancy was presumably caused by various influences, i.e., differences in the growth rate, type of stands, characteristics of the individual tree, age, genotype, topography, and site quality (Huh et al, 2020;Kim et al, 2020aKim et al, , 2020bPinto et al, 2004).…”
Section: Discussioncontrasting
confidence: 66%
“…Ramburan et al (2011) reported clay is generally considered an important site factor causing variation in cultivar responses in the interaction genotype by environment. However, in other species Lee et al (2022) reported that the growth of Pinus densiflora conditions were found to have a significant effect in the relationship between the annual ring growth and climate also in Korean Pine was significant different between microfibil angle with climate (Kim et al, 2020). tereticornis clones planted in southern China were 0.91 for tree diameter and heigth, as well as 0.87 for basic density (Yang et al, 2018).…”
Section: Growth Characteristics and Basic Densitymentioning
confidence: 95%
“…), pitch pines (P. rigida Mill), Keumkang pines (P. densiflora for. erecta), and sea pines (P. thunbergii) [19,20]. A substantial number of secondary metabolites such as terpenoids, phenolics, cinnamic acids, carboxylic acids, fatty acids, and flavonoids are present in pine needles [21].…”
Section: Introductionmentioning
confidence: 99%